The influence of various quenching parameters on the process of vacancy clustering in quenched pure aluminium - Du Preez, W. B.(Wilhelm Bouwer) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1980.